The Effects of Physical Restructuring on the Socioeconomic Status of Neighborhoods: Selective Migration and Upgrading - Merle Zwiers; Maarten van Ham; Reinout Kleinhans (Institute of Labor Economics (IZA), 2017)
In the last few decades, urban restructuring programs have been implemented in many Western European cities with the main goal of combating a variety of socioeconomic problems in deprived neighborhoods. The main instrument of restructuring has been housing diversification and tenure mixing. The demolition of low-quality (social) housing and the construction of owner-occupied or private-rented dwellings was expected to change the population composition of deprived neighbourhoods through the in-migration of middle and high income households. Many studies have been critical with regard to the success of such policies in actually upgrading neighborhoods. Using data from the 31 largest Dutch cities for the 1999 to 2013 period, this study contributes to the literature by investigating the effects of large-scale demolition and new construction on neighborhood income developments on a low spatial scale. We use propensity score matching to isolate the direct effects of policy by comparing restructured neighborhoods to a set of control neighborhoods with low demolition rates, but with similar socioeconomic characteristics. The results indicate that large-scale demolition leads to socioeconomic upgrading of deprived neighborhoods through the in-migration of middle and high income households. We find no evidence of spillover effects to nearby neighborhoods, suggesting that physical restructuring only has very local effects.
Keywords: O18; P25; R23; 330; urban restructuring; neighborhood change; selective migration; demolition